Computerized QT and QTc Measurements From Bedside ICU Monitors Are Similar to Those Derived From a Standard 12‐Lead ECG - Arthur Murray; Karolina Ho; Thomas J. Hoffmann; Gopika K. Ganesh; Shelvin Prasad; Sarah Berger; Cass Sandoval; Amy Larsen; Hildy Schell‐Chaple; Michele M. Pelter (Annals of Noninvasive Electrocardiology)
ABSTRACT QT/QTc prolongation is associated with an increased risk for torsade de pointes. In at‐risk hospitalized patients, it is common to obtain a standard 12‐lead electrocardiogram (ECG) for this assessment, but this interrupts patient care. Our hospital recently introduced bedside monitors in the intensive care unit (ICU) with continuous QT/QTc software. However, only four of the seven available ECG leads are used. Purpose Evaluate the agreement between computerized QT/QTc measurements from the bedside monitor (four leads) and a time‐matched standard 12‐lead ECG. Design Prospective observational study in three adult ICUs. Methods QT/QTc measurements were obtained from a convenience sample, and the two ECG types were ≤ 30 min apart. Agreement was evaluated using Bland–Altman analysis. Results A total of 120 patients were evaluated for inclusion, and 60 (50%) had a 12‐lead ECG for comparison. The mean bias difference for QT measurements was not statistically different (β = −2.47, 95% CI = 5.50 to −11.05; p = 0.44; limits of agreement (LOA) = −64.37 to 59.44). Similar non‐statistical differences were observed for QTc (β = −3.20, 95% CI = 5.50 to −11.05; p = 0.44; LOA = −67.43 to 61.03). Conclusion There was good agreement for both QT and QTc measurements between the two methods. These pilot data are promising and suggest QT/QTc measurements from bedside monitors (four leads) may be an acceptable alternative to obtaining additional standard 12‐lead ECGs. Given that half of the ICU patients screened did not have a 12‐lead ECG recorded, bedside monitor QT/QTc's could identify at‐risk patients. However, an evaluation in a larger sample and non‐ICU patients is warranted.